"My life's blueprint": publishing critical youth narratives in community-based organizations. Issue 1 (16th December 2019) - Lee, Crystal Chen; Schoonover, Nina R.
Abstract : Purpose: This paper aims to explore how currently underserved young adults engaged in a community-based organization (CBO), Bull City YouthBuild, wrote and published a book together, and how this work impacted them and their communities. Through a critical literacy framework, the research asked: How do students in a community-based writing project demonstrate self-empowerment and agency through narrative writing? Design/methodology/approach: This qualitative case study examined the students' published narratives. The researchers used ethnographic methods in data collection, and the qualitative data analysis approaches were developed through a critical conceptual framework. Findings: The students' narratives expressed self-empowerment and agency in the ways the young adults wrote against a dominant discourse; they wrote about repositioning their lives and redesigning their futures to reveal how they wanted to be externally perceived and to be leaders in their communities. The students expressed how the CBO offered them freedom to write their stories as they found new ways of using their historical and cultural backgrounds to collectively pursue success. Social implications: This work offers implications of how CBOs can meet the needs of currently underserved young adults through centering their voices. The authors see the writing process as crucial for student engagement in finding agency and self-empowerment with their words. Originality/value: Critical literacy foregrounds the voices of young adults as they push back against dominant narratives and stereotypes. This research hopes to reveal the intersections between CBOs and the communities they serve to develop literacies that are relevant and meaningful to young adults' lives.